Management of Peri-implant Mucositis of Multiple Osseointegrated Implants Using a Modified Free Gingival Graft “Punch Technique” in the Total Edentulous Area: A Case Report - Rosas, José (2020)
The purpose of this case report was to describe a technique to modify the free gingival graft by perforations within the graft to guarantee a horizontal increase in the keratinized mucosa in the anteroinferior sector of a total edentulous mandible after osseointegration of previously placed dental implants in a hybrid prosthesis protocol. A 71-year-old male underwent free modified gingival graft surgery with perforations at the level of each implant. At 3 months, the mucosa appeared to be healthy and keratinized, especially at a horizontal level around the implants previously diagnosed with mucositis, providing the patient with satisfactory results. Finally, the hybrid prosthesis was cleaned and polished due to the presentation of a hard plate at the level of the abutments. Within the limitations of this case report, further research is needed to evaluate the longterm efficacy of this modification to the free gingival graft.